Cellulose synthesis in two secondary cell wall processes in a single cell type - Mendu, Venugopal (Landes Bioscience, 2011)
Plant cells have a rigid cell wall that constrains internal turgor pressure yet extends in a regulated and organized manner to allow the cell to acquire shape. The primary load-bearing macromolecule of a plant cell wall is cellulose, which forms crystalline microfibrils that are organized with respect to a cell's function and shape requirements. A primary cell wall is deposited during expansion whereas secondary cell wall is synthesized post expansion during differentiation. A complex form of asymmetrical cellular differentiation occurs in Arabidopsis seed coat epidermal cells, where we have recently shown that two secondary cell wall processes occur that utilize different cellulose synthase (CESA) proteins. One process is to produce pectinaceous mucilage that expands upon hydration and the other is a radial wall thickening that reinforced the epidermal cell structure. Our data illustrate polarized specialization of CESA5 in facilitating mucilage attachment to the parent seed and CESA2, CESA5 and CESA9 in radial cell wall thickening and formation of the columella. Herein, we present a model for the complexity of cellulose biosynthesis in this highly differentiated cell type with further evidence supporting each cellulosic secondary cell wall process.